Re-constructing the conscious children's literature in the light of critical discourse analysis - Maceda, Emmanuel A.; Dizon, Leticia B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
This study explores the relationship of twenty-one specific texts of children's stories from the Adarna Children's Books and the ideologies being professed and perpetuated in the light of Critical Discourse Analysis (CDA). A comparative analysis between Ma. Bettina Soriano's findings found in her thesis "Social Values Depicted in the Aklat Adarna's International Edition Series: A Content Analysis" (1997) is utilized to establish how children's literature construct/re-construct/de-construct the subjectivity of a child. Soriano's statements are quoted verbatim and adjacent to this are variables that provide a counter-argument to Soriano's findings based on Louis Althusser's (1971) assumptions and Ian Parker's (1992) criteria in identifying discourses.
The results of this study reveals that generally, children's literature published by Adarna is supporting the Church, the School, the Family, and the State Hegemonic Ideological Apparatuses. It also exposes that children's stories as embodied by Adarna construct/re-construct/de-construct the subjectivity of a child through the employment of exaggerative expressions/illustrations and the reproduction and reinforcement of discursive practices of the Church, School, and Family Ideological State Apparatuses as well as the Patriarchal Society. The study does not recommend Adarna's Children's Books for children's reading as it operates under the panoptic of repressive Ideological State Apparatuses. It also recommends that librarians learn the various theories and methodologies in appraising literary works as well as the examination of other locally-published children's books.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Children's literature, Philippine -- History and criticism; Discourse analysis, Literary